Drivers of Real Exchange Rate in the Small Open Island of Mauritius (Global Journal of Human-Social Science, 2021)
This paper investigates the factors of real exchange rate (RER) in Mauritius by implementing a dynamic regression approach on quarterly data from 1999:Q1 to 2016: Q4. Productivity differential, interest rate differential, openness, gross domestic fixed capital formation and share price index are the main triggers of RER in the long-run. In the short-run, productivity differential and interest rate differential drive real exchange rate. Thus, RER will converge to its long-run equilibrium level if these factors are allowed to adjust freely.